Novel skin defense peptides and microbiota contribute to disease resilience of the Ngäbe-Buglé leopard frog - Douglas C. Woodhams; Douglas C. Woodhams; Aura Muñiz-Torres; Andreas Hertz; Patrick Kearns; Nina McDonnell; Laura Reinert; Louise A. Rollins-Smith; Louise A. Rollins-Smith; Brandon LaBumbard; Jamie Voyles; Corinne L. Richards-Zawacki; et al. (Frontiers in Amphibian and Reptile Science, 2024)
Some of the amphibian populations in Panama are demonstrating slow recovery decades after severe declines caused by the invasion of the fungal pathogen Batrachochytrium dendrobatidis (Bd). However, new species remain to be described and assessed for the mechanisms of disease resilience. We identified seven skin defense peptides from a presumably novel leopard frog species in the Tabasará range, at Buäbti (Llano Tugrí), Ngäbe-Buglé Comarca, and Santa Fe, Veraguas, Panama, herein called the Ngäbe-Buglé leopard frog. Two of the peptides were previously known: brevinin-1BLb from Rana (Lithobates) blairi and a previously hypothesized “ancestral” peptide, ranatuerin-2BPa. We hypothesized that the peptides are active against Bd and shape the microbiome such that the skin bacterial communities are more similar to those of other leopard frogs than of co-occurring host species. Natural mixtures of the collected skin peptides showed a minimum inhibitory concentration against Bd of 100 μg/ml, which was similar to that of other leopard frogs that have been tested. All sampled individuals hosted high intensity of infection with Bd. We sampled nine other amphibian species in nearby habitats and found lower prevalence and intensities of Bd infection. In addition to the pathogen load, the skin microbiomes were examined using 16S rRNA gene targeted amplicon sequencing. When compared to nine co-occurring amphibians, the Ngäbe-Buglé leopard frog had similar skin bacterial richness and anti-Bd function, but the skin microbiome structure differed significantly among species. The community composition of the bacterial skin communities was strongly associated with the Bd infection load. In contrast, the skin microbiome composition of the Ngäbe-Buglé leopard frog was similar to that of five North American leopard frog populations and the sympatric and congeneric Rana (Lithobates) warszewitschii, with 29 of the 46 core bacteria all demonstrating anti-Bd activity in culture. Because of the high Bd infection load and prevalence in the Ngäbe-Buglé leopard frog, we suggest that treatment to reduce the Bd load in this species might reduce the chytridiomycosis risk in the co-occurring amphibian community, but could potentially disrupt the evolution of skin defenses that provide a mechanism for disease resilience in this species.